Perceptions About The “Third Gender” In Nepal - Chhetri, Gyanu (Dhaulagiri Journal of Sociology and Anthropology, 2017)
This paper is built around the argument that negative attitudes of family and society towards the third gendered persons could lead to unacceptance, discrimination, exclusion and ostracization of the third gendered persons in the family and society. This paper presents an analysis of the causes of abandonment of one’s own family by the third gendered persons. Third Gendered Persons could open-up, come out and organize themselves for equality in par with other genders, when they get support from an organization. The third gendered persons in Nepal are getting organized under the umbrella of Blue Diamond Society. The Court recognition of third gendered persons as ‘natural’ people led the Government of Nepal consider the third gendered persons from ‘unnatural’ and ‘perverted’ to appoint a third gendered person a member of the Constituent Assembly. However, these people are not visible in the national census report. Same sex marriage is yet to be legalized. Dhaulagiri Journal of Sociology and Anthropology Vol.11, 2017; 96-114